Seasonality of immune‐mediated hemolytic anemia in dogs from southern California. (21st April 2014) - Kidd, Linda; Rasmussen, Rachel; Chaplow, Emilie; Richter, Keith; Hill, Steve; Slusser, Peter G.
Abstract Objective To determine if there is seasonal variation in the incidence of canine idiopathic immune‐mediated hemolytic anemia (IMHA) at 2 specialty hospitals in southern California. Design Retrospective study. To determine seasonality, cases of idiopathic IMHA presenting between June 2006 and June 2012 were identified by searching medical record databases of 2 large specialty hospitals. The presence of anemia with autoagglutination, spherocytosis or a positive Coomb's test and no identifiable underlying cause were required for inclusion. Dogs with a history of recent travel (within 1 year) were excluded. One hundred and twenty‐six dogs, 57 from a practice in San Diego, and 69 from a practice in Los Angeles, met the criteria. Results The pattern of seasonality differed with practice location (P = 0.02). More cases of idiopathic IMHA presented during spring and summer (n = 39) than winter and fall (n = 18) for the San Diego practice (P = 0.008) but not the Los Angeles practice (n = 32 and 37, respectively, P = 0.63). Conclusions The incidence of idiopathic IMHA in dogs presenting to specialty hospitals located in 2 different climates of southern California was different, suggesting environmental triggers may be involved. Larger, prospective studies are needed to determine whether environmental parameters or undetected infectious disease account for some cases of idiopathic IMHA in dogs.